Desenvolvimento de um sistema automatizado para a fabricação de filmes automontados - Trivinho-Strixino,Francisco (2004)
In this technical note, we describe the construction of a low-cost computer controlled device for layer-by-layer film fabrication. The software allows to control multiple material deposition, washing and drying steps and the time for each operation. To test the device, we produced and characterized self-assembled films of conductive polymers by alternating poly(o-methoxyaniline) (POMA) and poly(3-thiophene acetic acid) (PTAA) via the layer-by-layer technique.